Moderate rates of late Quaternary slip along the northwestern margin of the Basin and Range Province, Surprise Valley fault, northeastern California - Personius, Stephen F.; Crone, Anthony J.; Machette, Michael N.; Mahan, Shannon A.; Lidke, David J. (Journal of Geophysical Research-Solid Earth, 2009)
The 86-km-long Surprise Valley normal fault forms part of the active northwestern margin of the Basin and Range province in northeastern California. We use trench mapping and radiocarbon, luminescence, and tephra dating to estimate displacements and timing of the past five surface-rupturing earthquakes on the central part of the fault near Cedarville. A Bayesian OxCal analysis of timing constraints indicates earthquake times of 18.2 +/- 2.6, 10.9 +/- 3.2, 8.5 +/- 0.5, 5.8 +/- 1.5, and 1.2 +/- 0.1 ka. These data yield recurrence intervals of 7.3 +/- 4.1, 2.5 +/- 3.2, 2.7 +/- 1.6, and 4.5 +/- 1.5 ka and an elapsed time of 1.2 +/- 0.1 ka since the latest surface-rupturing earthquake. Our best estimate of latest Quaternary vertical slip rate is 0.6 +/- 0.1 mm/a. This late Quaternary rate is remarkably similar to long-term (8-14 Ma) minimum vertical slip rates (>0.4-0.5 +/- 0.3 mm/a) calculated from recently acquired seismic reflection and chronologic and structural data in Surprise Valley and the adjacent Warner Mountains. However, our slip rate yields estimates of extension that are lower than recent campaign GPS determinations by factors of 1.5-4 unless the fault has an unusually shallow (30 degrees-35 degrees) dip as suggested by recently acquired seismic reflection data. Coseismic displacements of 2-4.5 +/- 1 m documented in the trench and probable rupture lengths of 53-65 km indicate a history of latest Quaternary earthquakes of M 6.8-7.3 on the central part of the Surprise Valley fault.
id: 2021; PT: J; UT: WOS:000270058200001